The Role of the Patriot Program in Fostering Nationalism Among High School Students at SMAIT Peradaban Al Izzah in Sorong as a Strategy for Preventing Social Conflict in Papua: A Review of Ernest Renan’s Theory of Nationalism - Heru Sujaryanto; Winarno; Machmud Al Rasyid (Green Publisher Indonesia, 2026)
This condition affects the way the younger generation, especially Indigenous Papuan students, interpret their identity as part of the Indonesian nation. On the one hand, there is a historical narrative of inequality and marginalization that has developed in society, while on the other hand, the state seeks to strengthen national integration through education. This study aims to analyze the role of the Patriot Program in shaping student nationalism at SMAIT Peradaban Al Izzah in Sorong City. This study uses a qualitative approach with an ethnographic design in education. The data in this study were collected through several techniques, namely observation, in-depth interviews, and documentation. The results of the study show that the Patriot Program has an important role in shaping the nationalism of Indigenous Papuan students at SMAIT Peradaban Al Izzah in Sorong City through three main mechanisms: as an agent of socialization of national values that is dialogical and inclusive; as a medium of cross-ethnic interaction that encourages cooperation, reduces prejudice, and increases empathy between Papuan and non-Papuan students; and as a means of identity construction that allows the simultaneous integration of Papuan and Indonesian identities. These findings also show the relevance of Ernest Renan’s theory of nationalism, especially the concept of the nation as a “daily plebiscite,” which emphasizes the sustained will to live together. However, in the Papuan context, the theory needs to be complemented by a critical perspective that considers the factors of economic and political inequality in the process of forming nationalism.